2015
DOI: 10.1016/bs.pmbts.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Regulators of G Protein Signaling Proteins in Bone Physiology and Pathophysiology

Abstract: Regulators of G protein signaling (RGS) proteins enhance the intrinsic GTPase activity of α subunits of the heterotrimeric G protein complex of G protein-coupled receptors (GPCRs) and thereby inactivate signal transduction initiated by GPCRs. The RGS family consists of nearly 37 members with a conserved RGS homology domain which is critical for their GTPase accelerating activity. RGS proteins are expressed in most tissues, including heart, lung, brain, kidney, and bone and play essential roles in many physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 128 publications
(174 reference statements)
1
29
0
Order By: Relevance
“…Ca 2+ , as an intracellular second messenger, impacts nearly every aspect of biological processes through enormous versatility of Ca 2+ signaling . Components of Ca 2+ signaling, including Ca 2+ influx through Ca 2+ channel and Ca 2+ release from intracellular store, regulate the frequency and amplitude of Ca 2+ oscillations, which are critical for promoting osteogenesis . Our results showed that Ca 2+ oscillations were barely detectable in Rgs12 d/d OPCs (Fig.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Ca 2+ , as an intracellular second messenger, impacts nearly every aspect of biological processes through enormous versatility of Ca 2+ signaling . Components of Ca 2+ signaling, including Ca 2+ influx through Ca 2+ channel and Ca 2+ release from intracellular store, regulate the frequency and amplitude of Ca 2+ oscillations, which are critical for promoting osteogenesis . Our results showed that Ca 2+ oscillations were barely detectable in Rgs12 d/d OPCs (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Rgs proteins are broadly involved in bone development and remodeling via their influences on OC and OB differentiation and function individually or mutually . Our previous study demonstrated that Rgs12 promotes osteoclastogenesis during bone remodeling .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations